Women and Income Security in the Post-War Period: The Case of Unemployment Insurance, 1945-1962 - Porter, Ann (Labour/Le Travailleur, 1993)
This paper examines how women fared in the Canadian unemployment insurance scheme from the end of the World War II until the early 1960s. The implementation of UI in this period reinforced women's marginal economic position, as they were channelled into low-wage sectors and their access to income security benefits limited. The latter resulted, in particular, from a special UI regulation for married women, in effect from 1950 to 1957. The eventual revocation of this regulation can be attributed to changes in women's labour force participation, in their political representation in women's organizations and trade unions, and in attitudes concerning the proper role for women.